Love in the time of COVID‐19: A brief report on relationship and individual functioning among committed couples in the United States while under shelter‐in‐place orders. Issue 4 (27th July 2021) - Weber, Danielle M.; Wojda, Alexandra K.; Carrino, Emily A.; Baucom, Donald H.
Abstract: The COVID‐19 pandemic in the United States has changed many aspects of people's daily life, including increased time at home in response to shelter‐in‐place orders, heightened stress about health effects of COVID‐19, and shifts in other domains of life (e.g., employment). These lifestyle changes are likely to impact the well‐being of individuals and their romantic relationships. This investigation examined how COVID‐19 influenced couple and individual well‐being in real‐time during the early phase of the pandemic. Data were collected in early May 2020 during shelter‐in‐place orders in the United States. Participants in committed relationships ( n  = 332) completed an online survey assessing their experiences currently and before the pandemic. Results suggested that while couple functioning overall maintained or even improved, individual well‐being was more negatively impacted by the pandemic. Moreover, some groups who are at higher risk of a poor health outcome from COVID‐19 or experience unique challenges as a result of COVID‐19 reported worse outcomes (e.g., those whose employment changed) while others did not decline in their psychological and couple functioning (e.g., Black individuals and older individuals). These findings suggest that the pandemic has had varied impacts on couples and individuals, as well as across different virus‐related risk factors. Further research is needed to understand the nuanced effects of this pandemic on couples and individuals across time. Resumen: La pandemia de la COVID‐19 en los Estados Unidos ha cambiado muchos aspectos de la vida diaria de las personas, por ejemplo, el aumento del tiempo que pasan en sus hogares en respuesta a órdenes de confinamiento, un estrés más elevado por los efectos de la COVID‐19 en la salud, y cambios en otros aspectos de la vida (p. ej.: en el empleo). Estos cambios en el estilo de vida probablemente repercutan en el bienestar de las personas y en sus relaciones amorosas. En esta investigación se analizó cómo la COVID‐19 influyó en el bienestar de las parejas y de los individuos en tiempo real durante la primera fase de la pandemia. A principios de mayo de 2020 se recopilaron datos durante las órdenes de confinamiento en los Estados Unidos. Los participantes que estaban en relaciones de pareja estables ( n =332) contestaron una encuesta en línea donde se evaluaron sus experiencias de ese momento y las anteriores a la pandemia. Los resultados indicaron que, si bien el funcionamiento de la pareja en general se mantuvo o incluso mejoró, la pandemia afectó más negativamente el bienestar individual. Además, algunos grupos que tienen mayor riesgo de resultados desfavorables en la salud como consecuencia de la COVID‐19 o enfrentan dificultades singulares como resultado de la COVID‐19 informaron peores resultados (p. ej.: aquellos cuyos empleos cambiaron), mientras que otros no tuvieron un empeoramiento de su funcionamiento psicológico y de pareja (p. ej.: las personas de color y las personas mayores). Estos resultados sugieren que la pandemia ha tenido efectos variados en las parejas y en los individuos, así como entre los diferentes factores de riesgo relacionados con el virus. Se necesitan más investigaciones para comprender los efectos sutiles de esta pandemia en las parejas y en los individuos con el transcurso del tiempo. 摘要: 美国的COVID‐19大流行改变了人们日常生活的许多方面，包括应对就地避难命令致使的在家时间增多、对COVID‐19健康影响的压力增加，以及其他生活领域(如就业)的变化。这些生活方式的改变可能会影响个人的幸福和他们的恋爱关系。本调查研究了COVID‐19在大流行早期阶段如何实时影响夫妻伴侣和个人的福祉。数据于2020年5月初在美国的就地避难所收集。有承诺关系的参与者(n = 332)完成了一项在线调查，评估他们当前和新冠疫情大流行前的经历。结果表明，虽然伴侣的整体功能得到了维持甚至改善，但个人福祉受到了更大的负面影响。此外，一些因COVID‐19而健康状况不佳的风险较高的群体或因COVID‐19而经历独特挑战的群体报告了更糟糕的结果(例如，那些就业发生变化的群体)，而另外一些群体的心理功能和伴侣功能没有下降 (例如，黑人和老年人)。这些发现表明，大流行对夫妇和个人以及不同的病毒相关风险因素产生了不同的影响。需要进一步的研究来了解这场大流行在不同时期对夫妇和个人的微妙影响。